Perbandingan Soft Skill Menggunakan Model Pembelajaran GGE dan TSTS Memperhatikan Motivasi Berprestasi - Nurhidayani Yani; Edy Purnomo; Yon Rizal (JEE (Jurnal Edukasi Ekobis), 2017)
The purpose of this research was to know the difference of soft skill and the interaction of the use of cooperative learning model of group to group exchange and two stay two stray type by considering achievement motivation. The methodology in this research was quasi experiment with comparative approach. The study design used treatment by level design. The population were 4 classes and the samples used by 2 classes in Islamic Junior high School Tias Bangun, classes was determined through random cluster sampling. Data collection technique used observationand questionnaires. Hypothesis testing using two-way analysis of variance and t-test two independent sampels. Based on data analysis, it obtained the result that there is a difference in soft skill and the interaction of the use of cooperative learning model of group to group exchange and two stay two stray write type by considering achievement motivation.Tujuan penelitian ini untuk mengetahui perbedaan soft skill dan interaksi penggunaan model pembelajaran kooperatif tipe group to group exchange dan two stray two stay dengan memperhatikan motivasi berprestasi. Metode yang digunakan adalah eksperimen semu dengan pendekatan komparatif. Desain penelitian yang digunakan treatment by level design. Populasi dalam penelitian ini sebanyak 4 kelas dan sampel sebanyak 2 kelas di SMP Islam Tias Bangun yang ditentukan melalui cluster random sampling. Teknik pengumpulan data melalui pengamatan dan angket. Pengujian hipotesis menggunakan analisis varians dua jalan dan t-tes dua sampel independen. Berdasarkan analisis data diperoleh hasil bahwa ada perbedaan soft skill dan interaksi penggunaan model pembelajaran kooperatif tipe gge dan tsts dengan memperhatikan motivasi berprestasi.Kata kunci: motivasi berprestasi, soft skill, group to group exchange, two stay two stray